Comparison of endocervical and endometrial cytology to diagnose sub- clinical endometritis in repeat breeding cows - A. Ganesan; S. Satheshkumar; M. Murugan; A. Palanisammi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Repeat breeding due to sub clinical endometritis (SCE) is often diagnosed by cytological examination and the effect of endocervical inflammation (ECI) on increased hazards ofpregnancy is inadequately investigated. In this study, endocervical cytology was compared with the golden standard test `endometrial cytology’ to detect SCE as a cause of repeat breeding in cows. Influx of Neutrophils and endocervical inflammation will reflect the status of endometrium and may indirectly reflects the ongoing sub clinical form of endometrial inflammation. Hence, this study was aimed at fixing threshold for PMN in endocervical cytology and comparing the same with golden standard technique. Repeat breeding cows associated with endocervical inflammation with >8% of neutrophils during standing estrus in endocervical cytology will have increased hazards of pregnancy. Our study suggested that a moderate concordance/association between ECI and endometrial inflammation (EDI) in repeat breeding cows, these findings were based on the endocervical and endometrial cytology. Based on the endocervical cytology examination 85% of repeat breeding cow posses EDI (SCE) with a diagnostic sensitivity of 86% and showing moderate clinical acceptability for application of endocervical cytology as diagnostic aid to detect SCE in repeat breeding cows.